Bibliometric Study on the Influence of Digital Technology in the Field of Arts and Culture - Mardiani, Eri; Rukmana, Arief Yanto; Maqfirah, Poetri AL-Viany; Nuswantoro, Patriandi; Uhai, Sabalius (The Eastasouth Journal of Social Science and Humanities, 2024)
This bibliometric study delves into the impact of digital technology on the field of arts and culture through a systematic examination of scholarly literature. By employing bibliometric methodologies, the research identifies key themes, trends, and gaps in existing research, shedding light on the multifaceted influence of digital innovation in artistic creation, distribution, preservation, education, and industry dynamics. Through data collection, extraction, and analysis, the study reveals evolving research patterns over time and offers insights into potential avenues for future inquiry. The findings contribute to a deeper understanding of the dynamic relationship between technology and cultural expression, informing decision-making and inspiring innovative practices in the digital age.